Pelatihan Penggunaan E-Commerce Shopee dan Sosial Media sebagai Alat Pemasaran Produk - Huda, Moch. Faizul; Febriyansah, Yunus; Karimah, Maulida Dini; Romantika, Meliya Ayu; Alqaedah, Alifiyah (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Digital marketing is a marketing strategy to promote a business, brand or business by utilizing digital media. Through digital-based media, businesses gain access to resources that are otherwise unavailable to business owners, including the people living in Seketi Village, Jombang. One of the community groups in Seketi Village which operates in the business sector is the Asman Group. Implementation of service activities carried out by the team of University of KH. A. Wahab Hasbullah is product marketing training and community business improvement. This training activity uses a face-to-face/offline meeting method between resource persons and partners located at the Seketi Village Hall office, Mojoagung District, Jombang Regency. The implementation of this service program in the form of "Training on the Use of Shopee E-Commerce and Social Media as a Tool for Marketing Products" includes several strands, namely Identifying Community Needs, Creating Shopee and Instagram Accounts, Operational Assistance and Implementation of Shopee E-Commerce Accounts and Instagram Accounts for Partner. The results of this activity can be seen from the training participants' understanding of marketing on E-Commerce and social media. Participants indirectly learned that marketing on social media and E-Commerce can reach a wider market and is easily accessible to anyone.